A development of novel Ni–P coating on anodised aluminium alloys for military industries applications in artificial sea water. (2nd December 2019) - Abdel-Gawad, Soha A.; Osman, Walid M.; Fekry, Amany M.
ABSTRACT: The corrosion behaviour and characterisation properties of a novel Ni–P coating on anodised aluminium alloys were inspected by utilising a salt spray technique and a polarisation system in artificial sea water. The Ni–P layer on anodised coating progression was achieved on aluminium alloys such as Al2014, Al6061 and Al7075, which are utilised in military industries. The outcomes revealed that the coating layer is contingent on the alloy type and coating settings like current density, temperature and time. Also, film thickness and hardness of aluminium alloys have been considered. The corrosion rate was established to be dependent on the alloying element such as copper. The deterioration rates of Al7075 and Al6061 were diminished by about one order of magnitude; however, for Al2014, it was amplified by an equivalent order of magnitude.